Tectonostratigraphic evolution of the Orphan Basin and Flemish Pass region – Part 1: Results from coupled kinematic restoration and crustal area balancing. (June 2021) - Cawood, Adam J.; Ferrill, David A.; Morris, Alan P.; Norris, David; McCallum, David; Gillis, Erin; Smart, Kevin J.
Abstract: The Orphan Basin and Flemish Pass region on the Newfoundland continental margin is a frontier area in terms of oil and gas exploration and remains poorly understood in terms of structural evolution and rift development. The area has few exploration wells and, until recently, sparse seismic data coverage. Existing gravity inversion and seismic refraction data from the area suggest that stretched continental crust in the Orphan Basin is highly attenuated (locally to < 5 km) but previously published structural restorations have been unable to fully restore the continental crust below the Orphan Basin to pre-deformed thicknesses (30–32 km). Here we perform a structural restoration of a regional, WNW-ESE oriented cross-section to investigate crustal structure, rifting style, and structural evolution of the Orphan Basin and Flemish Pass region. Interpretation is constrained by modern regional depth converted broadband 2D and 3D seismic reflection data, well data, and published gravity inversion results. Present-day crustal thicknesses are used as constraints for crustal area balancing and estimation of crustal thinning across the basin. We find that low-angle extensional detachments are widespread in the area, with offsets on individual structures of up to 42 km. Zones of attenuated continental crust are coincident with the presence of low-angle detachment surfaces displaying isostatic uplift of detachment footwalls. Comparison of total extension derived from crustal area balancing vs. structural restoration suggests approximately 39% of extension across the cross-section is unresolvable in seismic data. We attribute this to (i) ductile deformation prior to brittle faulting, (ii) subseismic-scale faulting, (iii) uncertainties in detachment breakaway positions, and (iv) unresolvable later offset of detachment surfaces. Widespread and relatively evenly distributed extension across the Orphan Basin and Flemish Pass region from Middle-Late Jurassic to Early Cretaceous influences sediment distribution across the region. Calibrated regional seismic mapping of the Orphan Basin suggests that significant thicknesses of Jurassic strata exist throughout the area, including in the northwestern part of the study area, where Kimmeridgian and Tithonian strata reach combined thicknesses of up to 4.9 km. Highlights: Significant thicknesses of Jurassic strata identified throughout the Orphan Basin and Flemish Pass. Kinematic restoration and crustal area balancing used to constrain timing and amount of extension across the study area. Structure dominated by low-angle extensional detachments with offsets on individual structures of up to 42 km. Attenuated continental crust is coincident with low-angle detachment surfaces and isostatic uplift of detachment footwalls.